META ANALISIS PENGARUH METODE PROBLEM BASED LEARNING DALAM PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Istiawan, Aziz Mahendra; Laila, Alfi; Aka, Kukuh Andri (Tarbiyatuna Kajian Pendidikan Islam, 2022)
The purpose of this study was to analyze the effect of the PBL (Problem Based Learning) model in learning mathematics. The PBL (Problem Based Learning) model is a learning model that presents a variety of authentic and meaningful problems to students which serves as an investigation and investigation. The method used in this study is a meta-analysis method using a sample of five 2015-2020 national journal articles.